Analisa Pengendalian Persediaan Bahan Baku Bumbu Racik Makanan dari Raw Material Hingga Barang Jadi (Finish Good) di PT. Ariake Europe Indonesia - Almadali Dahari; Dene Herwanto; Jauhari Arifin (Jurnal Ilmiah Wahana Pendidikan, 2021)
PT. Ariake Europe Indonesia is one of the companies that has a focus on the food seasoning industry. The seasoning products produced by the company are Chicken Meat Powder and Kril Extract, these products are condiments that have the flavor of chicken. then the seasonings that have been produced are distributed to various retail or spice mix shops in the Jabodetabek area, apart from the Indonesian market, this company is also distributed to Japan. In carrying out the production process, the company always needs raw materials, while in the inventory of these raw materials, unexpected problems often occur, such as a shortage of raw materials which causes the production process to not run smoothly and employees are forced to be transferred to other production departments to work on this type of production. other spices. In addition, there has been an overproduction which resulted in the capacity in the warehouse being piled up. Therefore, to avoid bottlenecks in the production process, it must be balanced with the availability of good (optimal) raw materials. Based on the existing background, it can be formulated the problem that wants to be raised, namely "Analyzing the flow of the inventory control system for raw material ingredients for food preparation from raw materials to finished goods (finish good) PT. Ariake Europe Indonesia".